Chemostratigraphy of Sediments in Benin West -1, Benin Flank: Paleoenvironmental Implications - Odedede, O. (Journal of Scientific Research, 2016)
Chemostratigraphical study was carried out on sediments of Benin west -1 well in order to understand their paleoenvironmental setting and geochemical zonations. Six chemozones (CHM 1, CHM 2, CHM 3, CHM 4, CHM 5 and CHM 6) were recognized in the stratigraphic column. Sedimentological attributes and maxima peaks and / or fluctuating trends of Zn, SiO2, K2O, Sr adjudged CHM 3 zone as a potential lowstand systems tract. Synergy of sedimentological and chemostratigraphical fingerprints suggests a marine to distributary channel environment of deposition.